Immune system alteration in response to increased physical training during a five day soccer training camp - Malm, C.; Ekblom, Ö.; Ekblom, B. (International Journal of Sports Medicine, 2004)
Leukocyte and monocyte subpopulations were investigated in ten elite male soccer players before and after a 5-day training camp. It was hypothesized that with increased training intensity and duration, the immune system would show signs of depression. Blood samples were taken at rest before and after the training camp and cell surface antigens were investigated by four-colour flow cytometry. After five days of intensified training, there was a significant decrease in the number of T helper, T cytotoxic and B cells, the expression of CD11 b on leukocytes increased and the NK cell population did not change significantly. It is concluded that after a period of intensified training, soccer players may experience decreased T and B cell numbers in circulation, possibly affecting their capability to activate the immune system and resist infections. However, in contrast to the acute decrease in the number of circulating NK cells commonly observed after physical exercise, no change in this cell population was observed at rest after a period of intensified physical training. Exercise-induced immunological changes were highly differentiated between different leukocyte subpopulations.